Pemanfaatan Tanaman pada Upacara Adat Pernikahan Suku Melayu di Desa Sutera Kecamatan Sukadana Kabupaten Kayong Utara - Fahmi, Annisa Aulia; Turnip, Masnur; Rafdinal, Rafdinal (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The traditional wedding ceremony has become a tradition for the Malay Tribe Community in Sutera Village, Sukadana District, North Kayong Regency, which has long been carried out from generation to generation. The tradition of carrying out this wedding has undergone many changes both in the procession and the plants used. This study aims to determine the types of plants and plant parts used by the Malay Tribe Society in Sutera Village, Sukadana District, Kayong Utara District. The research was conducted by conducting semi-structured interviews with 15 respondents, the method of selecting respondents used snowball sampling. Based on the research results, it is known that the Malay Malay community in Sutera Village, Sukadana District, Kayong Utara Regency utilizes 26 types of plants for traditional wedding ceremonies, which belong to 20 families. Poaceae and Zingiberaceae are one of the plant families that are widely used by the community for traditional wedding ceremonies. The part of the plant that is widely used is the leaf (34%). This research shows that the plants used in traditional wedding ceremonies of the Kayong Utara Malay Community have an important value in each process.